PENGARUH VARIASI KONSENTRASI NaCl PADA TAHAP PENCUCIAN TERHADAP SIFAT FISIKOKIMIA SURIMI-BASED PRODUCT AYAM BROILER - Hardyawan, Stevanus; Matoetina, Maria; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2012)
Surimi-based product is a white meat protein extract based products. The protein was obtained from washing process where the kind of protein fraction depends on the type and concentration of the solution washing. Therefore need to study the influence of NaCl concentration used in washing process on the physicochemical properties. This study used a randomized block design with surimi-based product NaCl concentration (PN) consists of 6 level 0.1; 0.2; 0.3; 0.4; 0.5; and 0.6%, which was repeated three times. The parameters was the physicochemical properties of surimi-based product consist of the gel quality (gel strength and folding test), thaw-drip, water holding capacity, water content. The effects were analyzed uses ANOVA followed by DMRT for the one that save significant effect. The results showed that the NaCl concentration gave significant effect to the water content and water holding capacity of meat porridge II, gel strength and folding test of surimi-based product. The higher concentration of NaCl the lower water content of the meat slurry II (82.6418% - 74.4874%), water holding capacity of meat slurry II (71.4175% - 59,4225%), gel strength (3851.082 g.s - 2381.608 g.s) and folding test (15382.186 g.s - 26955.768 g.s), but the higher the thaw-drip (2,0583% - 5,3603%) . Gel strength and folding test graph were quadratic curve. The increase concentration of NaCl in the washing stages reduce the water binding capacity of the protein because of leaching in washing solution so that the reduced strength and elasticity of chicken surimi-based products.